OC-020 Validation of the utility of a faecal immunochemical testfor haemoglobin (fit) in patients presenting to primary care with new bowel symptoms. (17th June 2017) - Digby, J; Mowat, C; Steele, RJC; Strachan, JA
Abstract : Introduction: Symptoms alone are poor predictors of underlying colonic pathology. 1 Yield of significant bowel disease (SBD), [colorectal cancer (CRC), high risk adenoma (HRA, defined as ≥3 or any ≥1 cm) and inflammatory bowel disease (IBD)] is low in patients referred for colonoscopy from primary care at 14%. 2 We have shown that undetectable Faecal Haemoglobin (fHb) as measured by a faecal immunochemical test (FIT) is a good rule-out test for SBD. 2, 3 We introduced FIT tests to primary care in NHS Tayside from 7 th December 2015 and report the impact on referral rates and the yield of SBD at colonoscopy from data collected up to 30 th September 2016. Method: Patients in primary care with new bowel symptoms were encouraged to complete a FIT in addition to blood count and renal function check. FIT tests were analysed in Blood Sciences (HMJACKarc, Kyowa Medex Co. Ltd., Japan) to give fHb within a range of <10 to>400 µg Hb/g faeces. Referral rates with FIT were examined along with clinical findings at colonoscopy. Results: 4261 FIT kits were analysed (median age 64 years (range: 2–98, IQR: 51–75), 56% female). 3246 (76%) had undetectable fHb, 911 (21%) had detectable fHb and 2.4% were untestable. 1988 patients completed a FIT but were not referred, with 1855 (93.3%) having undetectable fHb. Referrals to the Colorectal Service were 14% lower than in the corresponding time period of the preceding year. 3512 patients were referred; 1925 (55%) had completed a FIT. Of the 924 patients with a FIT result plus colonoscopy, 43% had undetectable FIT, 41% detectable up to 400 µg Hb/g faeces and 16%>400 µg Hb/g faeces. There were 203 cases of SBD (22%); 58 CRC, 87 HRA, 58 new cases of IBD. 33% of those with any fHb had SBD compared with 7% of those with undetectable fHb. Furthermore, of 150 patients who had fHb >400 µg Hb/g faeces, 88 (55%) had SBD. Conclusion: Undetectable fHb is offering reassurance that SBD is unlikely and referrals to the Colorectal Service have reduced. At colonoscopy, yield of SBD has increased and is highest in those with detectable fHb. FIT testing is an essential adjunct to the history, examination and blood tests in the assessment of bowel symptoms. References: . Jellema P, van der Windt DAWM, Bruinvels DA, et al. Value of symptoms and additional diagnostic tests for colorectal cancer in primary care; systematic review and meta-analysis. BMJ2010;340:c1269. . Mowat C, Digby J, Strachan JA et al. Faecal haemoglobin and faecal calprotectin as indicators of bowel disease in patients presenting to primary care with bowel symptoms. Gut 2016;65(9):1463–9. . McDonald PJ, Digby J, Innes C et al. Low faecal haemoglobin concentration potentially rules out significant colorectal disease. Colorectal Dis 2013;15:e151-9. Disclosure of Interest: None Declared